2016
DOI: 10.1007/s12282-016-0690-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, an inhibitory agent in breast cancer

Abstract: The broad inhibitory effects of melatonin in breast cancer make it a promising agent and may add it to the list of potential drugs in treatment of this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 72 publications
(124 reference statements)
3
52
0
3
Order By: Relevance
“…Melatonin, including at physiological concentrations (1 nM) exerts cytotoxic, anti-mitotic and pro-apoptotic actions in these cells [40,202,203]. That melatonin has antiproliferative functions have been validated in both ERα-positive and ERα-negative human breast cancer cell lines [179,204].…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
“…Melatonin, including at physiological concentrations (1 nM) exerts cytotoxic, anti-mitotic and pro-apoptotic actions in these cells [40,202,203]. That melatonin has antiproliferative functions have been validated in both ERα-positive and ERα-negative human breast cancer cell lines [179,204].…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
“…12 The indoleamine has great pharmacological promise as an antioxidant enzyme that can scavenge free radicals, and protect from oxidative damage. 13,14 Previous studies has shown that melatonin can inhibit the proliferation of various human cancers, including leukemia, 15,16 hepatocarcinoma, 17 breast cancer, 18 colorectal cancer, 19,20 lung cancer, 21,22 and gastric carcinoma. 23,24 However, studies investigating the molecular link between the UPR and autophagy activation by melatonin in GC are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (MT) has been shown to function as an antiestrogenic agent, and only for this reason should be considered for BC treatment [217,221] (Table 2). Sonehara et al, have shown that treatment with MT modulates tumor aggressiveness, increasing apoptosis under microenvironmental acidosis in BC cell lines [222].…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%